Analysis of the three-dimensional vector facade model created from photogrammetric data - Seredovich, V.; Kamnev, I. (КНУБА, 2018)
The results of the accuracy assessment analysis for creation of a threedimensional vector model of building façade are described. In the framework of the analysis, analytical comparison of three-dimensional vector façade models created by photogrammetric and terrestrial laser scanning data has been done. The threedimensional model built from TLS point clouds was taken as the reference one. In the course of the experiment, the three-dimensional model to be analyzed was superimposed on the reference one, the coordinates were measured and deviations between the same model points were determined. The accuracy estimation of the threedimensional model obtained by using non-metric digital camera images was carried out. Identified façade surface areas with the maximum deviations were revealed.
Аналіз тривимірної векторної моделі фасаду, створеної за фотограмметричними даними
Анализ трехмерной векторной модели фасада, созданной по фотограмметрическим данным
Keywords: terrestrial laser scanning; ground-based photogrammetry; accuracy estimation; non-metric digital cameras; three-dimensional model; 528.71:528.8